Individual to Collective Knowledge: Interaction, Interpretation and Integration (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2019)
This article is based on the hypothesis that the transformation of knowledge, both individually and collectively, can be achieved through interaction and is supported by processes of interpretation and integration. In this sense, the contribution of this article is materialized in: 1) a proposal for the application of mechanisms that facilitate the interaction, interpretation and integration of knowledge. 2) It extracts elements from the analysis of a method that facilitates the understanding of the flow of knowledge. 3) It proposes six control points oriented to the measurement of the change of state.